MFN2 Prevents Neointimal Hyperplasia in Vein Grafts via Destabilizing PFK1. Issue 11 (22nd April 2022) - Tang, Yuanjun; Jia, Yiting; Fan, Linwei; Liu, Han; Zhou, Yuan; Wang, Miao; Liu, Yuefeng; Zhu, Juanjuan; Pang, Wei; Zhou, Jing
Abstract : Background: Mechanical forces play crucial roles in neointimal hyperplasia after vein grafting; yet, our understanding of their influences on vascular smooth muscle cell (VSMC) activation remains rudimentary. Methods: A cuff mouse model was used to study vein graft hyperplasia. Fifteen percent to 1 Hz uniaxial cyclic stretch (arterial strain), 5% to 1 Hz uniaxial cyclic stretch or a static condition (venous strain) were applied to the cultured VSMCs. Metabolomics analysis, cell proliferation and migration assays, immunoblotting, co-immunoprecipitation, mutagenesis, pull-down and surface plasmon resonance assays were employed to elucidate the potential molecular mechanisms. Results: RNA-sequencing in vein grafts and the controls identified changes in metabolic pathways and downregulation of mitochondrial protein MFN2 (mitofusin 2) in the vein grafts. Exposure of VSMCs to 15% stretch resulted in MFN2 downregulation, mitochondrial fragmentation, metabolic shift from mitochondrial oxidative phosphorylation to glycolysis, and cell proliferation and migration, as compared with that to a static condition or 5% stretch. Metabolomics analysis indicated an increased generation of fructose 1, 6-bisphosphate, an intermediate in the glycolytic pathway converted by PFK1 (phosphofructokinase 1) from fructose-6-phosphate, in cells exposed to 15% stretch. Mechanistic study revealed that MFN2 physically interacts through its C-terminus with PFK1. MFN2 knockdown or exposure of cells to 15% stretch promoted stabilization of PFK1, likely through interfering the association between PFK1 and the E3 ubiquitin ligase TRIM21 (E3 ubiquitin ligase tripartite motif [TRIM]-containing protein 21), thus, decreasing the ubiquitin-protease-dependent PFK1 degradation. In addition, study of mechanotransduction utilizing pharmaceutical inhibition indicated that the MFN2 downregulation by 15% stretch was dependent on inactivation of the SP1 (specificity protein 1) and activation of the JNK (c-Jun N-terminal kinase) and ROCK (Rho-associated protein kinase). Adenovirus-mediated MFN2 overexpression or pharmaceutical inhibition of PFK1 suppressed the 15% stretch-induced VSMC proliferation and migration and alleviated neointimal hyperplasia in vein grafts. Conclusions: MFN2 is a mechanoresponsive protein that interacts with PFK1 to mediate PFK1 degradation and therefore suppresses glycolysis in VSMCs.